Pengaruh Jangka Waktu Perebusan terhadap Rendemen dan Beberapa Karakteristik Minyak Kelapa Sawit - Aghnia Rahmawati; Kelik Putranto; Hendrawan Hendrawan; Eko Wahyudin (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2023)
The processing of crude palm oil aims to produce maximum result. However, there is a problem in processing of crude palm oil that is to determine the right boiling period according to temperature. The boiling period effects the separation speed of the oil from water and dirt so that determine the quality of crude palm oil. Research about the effect of boiling period on yield and some characteristics of crude palm oil had been conducted with the treatments were boiling periods 1, 1.5, 2, 2.5, 3, and 3.5 hours. The experiment took place at the Laboratory of Agriculture Faculty UICM and at the Chemistry Laboratory of Food Technology Ma’soem University. Characteristics observed were yield percentage, moisture content, free fatty acid content, and impurity determination. The objective of the research was to determine the right boiling period in order to produce the best characteristic of CPO. The experimental randomized block design was applied and every treatment was repeated four times. Result of the research showed that the boiling period of 2 hours was the best with yield percentage 71.83%, free fatty acid 2.20%, moisture content 4.77% and impurity 4.86%.